Diagnosis, Physical Exam, and Imaging for Osteochondral Lesions of the Talus (Foot & Ankle Orthopaedics, 2018)
Category: Ankle Introduction/Purpose: Cartilage lesions of the talus are a challenging clinical pathology for orthopaedic surgeons. To date, the treatment guidelines for these lesions have been based on both low quality and low levels of evidence. Therefore, an international consensus group of experts was convened to collaboratively advance toward consensus opinions on key topics regarding cartilage lesions of the talus. Diagnosis, physical exam and imaging were discussed as one portion of the first International Consensus Meeting on Cartilage Repair of the Ankle. The purpose of this abstract is to explain the process and delineate the consensus statements derived from this consensus meeting on the diagnosis, physical exam and imaging for osteochondral lesions of the talus. Methods: 75 national and international experts in cartilage repair of the ankle, representing 25 countries and all six continents, were convened and participated in a process based on the Delphi method of achieving consensus. Experts were assigned to groups separated by topics, including diagnosis, physical exam and imaging. Questions and statements were drafted within the groups and a comprehensive literature review was performed and, where possible, used to confirm or dispute the recommendations made. In addition, the available evidence for each statement was graded. Once the statements achieved majority vote within the working groups, a vote to the overall group was undertaken. The statements were then further edited on the basis of the discussion and votes within the entirety of the consensus group. A final vote then occurred, and the strength of consensus was characterized as follows: consensus: 51 - 74%; strong consensus: 75 - 99%; unanimous: 100%. Results: 12 statements addressing diagnosis, physical exam and imaging for cartilage lesions of the talus reached some degree of consensus. These included conclusions on how suspected lesions should be evaluated. There was a consensus that: [1] Weight-bearing AP, lateral, and mortise radiographs should be utilized to evaluate a known or suspected cartilage lesion of the ankle. [2] Lesion size should be estimated in three planes including surface area and depth of the lesion. [3] If precise measurement is required including depth, the use of CT is recommended, but for daily practice, a size estimate using MRI is appropriate. [4] Diagnostic arthroscopy is of limited value and seldom influences treatment approach in the assessment of a known or suspected cartilage lesion of the ankle. Conclusion: There is a lack of evidence-based guidelines available to direct treatment for clinicians when managing cartilage lesions of the ankle. This international consensus derived from leaders in the field will assist clinicians with a combination of expert- and evidence-based guidelines to consider in the evaluation of a cartilage lesion of the talus including diagnosis, physical exam and imaging.